PREFERENCYJNA OPCJA NA RZECZ UBOGICH JAKO WYRAZ MIŁOŚCI SPOŁECZNEJ - Surmiak, Wojciech (Studia Pastoralne, 2023)
This article presents the issue of the preferential option for the poor that appears to be a natural consequence of the social love. At first the author presents poverty as an expression of a great injustice in the world and later on points at historic origins and evolution of the preferential option for the poor presented in the Catholic social teaching. In the final part of the article the author reflects upon the question, whether the option for the poor is a theological passe, or still constitutes a living element of the social teaching of the Church especially with its regards to relation between justice and love.